High PIB Retention in Alzheimer's Disease is an Early Event with Complex Relationship with CSF Biomarkers and Functional Parameters - Forsberg, A.; Almkvist, O.; Engler, H.; Wall, A.; Langstrom, B.; Nordberg, A. (Current Alzheimer Research, 2010)
Background: New in vivo amyloid PET imaging tracers, such as 11C-PIB, provide possibilities to deeper understand the underlying pathological processes in Alzheimer's disease (AD). In this study we investigated how 11C-PIB retention is related to cerebral glucose metabolism, episodic memory and CSF biomarkers. Method: Thirty-seven patients with mild AD and 21 patients with mild cognitive impairment (MCI) underwent PET examinations with the amyloid tracer 11C-PIB, 18F-FDG for measurement of regional cerebral metabolic rate of glucose (rCMRglc), assessment of episodic memory and assay of cerebral spinal fluid (CSF) levels of amyloid-ß (Aβ1-42), total tau and phosphorylated tau respectively. Analyses were performed using Statistical Parametric Mapping (SPM) and regions of interest (ROIs). Results: Pooled data from AD and MCI patients showed strong correlations between 11C-PIB retention, levels of CSF biomarkers (especially Aß1-42), rCMRglc and episodic memory. Analysis of the MCI group alone revealed significant correlations between 11C-PIB retention and CSF biomarkers and between CSF biomarkers and episodic memory respectively. A strong correlation was observed in the AD group between rCMRglc and episodic memory as well as a significant correlation between 11C-PIB retention and rCMRglc in some cortical regions. Regional differences were observed as sign for changes in temporal patterns across brain regions. Conclusions: A complex pattern was observed between pathological and functional markers with respect to disease stage (MCI versus AD) and brain regions. Regional differences over time were evident during disease progression. 11C-PIB PET and CSF Aß1-42 allowed detection of prodromal stages of AD. Amyloid imaging is useful for early diagnosis and evaluation of new therapeutic interventions in AD.
Keywords: C-PIB-PET